Impact of COVID-19 in social, physical and functional quality of life among reproductive female patients - Mahajabin, Progga; Sultana, Zakia; Islam, M. Ziaul; Sarmin, Tanjina; Parvin, M. Maksuda; Aktar, Mossa Nupur; Zubery, M. Husnaion; Rahman, Falguni Binte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Those who recovered from the COVID-19, suffers various health-related as well as mental problems. To measure a person’s disease impact, disability, and mental condition, health-related quality of life (HRQoL) is used. The aim of this study was to assess the state of health-related quality of life of women of reproductive age after recovery from COVID-19. Methods: This cross-sectional study was conducted in Department of Reproductive and Child Health, National Institutes of Public Health and Social Medicine in Mohakhali, Dhaka, Bangladesh, during the period from January to December 2020. Total 202 women of reproductive age who were recovered from COVID-19 were included in this study. Results: In this study, majority of the women (46%) were within 36-50 years and majority (20.8%) had bronchial asthma. Most of the respondents suffering from COVID-19 from 15 days to 3 months (43.6%). In a study, the average HRQOL score among respondents was 66.01 (±11.81), with physical well-being scoring highest (19.89±4.41) and functional well-being lowest (14.44 ±4.19). Age-wise, respondents aged 15-25 scored highest in various health domains. Statistical analysis revealed significant differences in Fact-G scores across age groups, with 15-25-year-olds scoring highest, indicating a notable age-related variation in health quality. Conclusions: Findings of the study shows that fifteen to twenty-five years’ age of women’s HRQOL was higher than other groups. Educated women have better HRQOL score. Physical wellbeing was higher than other domains and functional wellbeing was lower than other domains. Elderly women who had comorbidities had lower HRQOL score.